Dosis dan Waktu Aplikasi Boron Terhadap Pertumbuhan dan Hasil Kacang Hijau - Krisna Cahya Nurani; Susilo Budiyanto; Endang Dwi Purbajanti (Agrosains : Jurnal Penelitian Agronomi, 2020)
Green beans are legume plants that are in great demand because of their high nutrition content and include plants that require boron to support growth from the vegetative to generative phase. The study aims to assess the growth and production of green beans due to influence of the dose and time of boron application. The research was carried out using completely randomized design with factorial pattern 3×3 with 3 replications. The first factor was the treatment of boron doses of 1, 1.5, and 2 kg/ha was given once at 7 Day After Planting (DAP), fertilizer application twice at 7 and 28 DAP, and once given at 28 DAP. The results showed that dose of boron at a dose of 1 kg/ha was able to produce the number of affective root nodules and the best pod weight. The treatment of boron once at 7 DAP can increase plant height, flowering age, pod weight, and seed weight per pod. The interaction between dose and time of boron application affects the number of affective root nodules and seed weight per pod.